THE WINTER'S TALE BY WILLIAM SHAKESPEARE IN THE CONTEXT OF ENGLISH CULTURAL AND SOCIAL PAST - Mišić, Danijela (Metodička teorija i praksa, 2025)
By reading Shakespeare’s play The winter’s tale in a new way the author of this paper has the goal to focus our attention on the actual events and the connection between the events from social reality and from personal, emotional, spiritual world of characters. The author’s aim is to show that the past brings energy to present time and for ideas of cosmic justice  that must be satisfied in every moment by no means. By linguistic analyses, thinking about characters’ actions, by revealing hidden meaning of the spoken words, by citing chosen extracts from the play we come to the conclusion that the past leaves an indelible mark in the present and has a noticable influence on today’s society and culture. Verse narration reveals Shakespeare’s attitude towards tradition, customs and faith striving towards harmony and love for people and for God. Shakespeare finds the material for this play in real life, but the focus of his dramatic enthusiasm is a man himself – a timeless being with universal fears, anxieties and sufferings, who is torn apart between his inner thoughts and knowledge of the outer world. This very fact is actually a testimony of eternal spiritual makeover, changes of ideas and knowledge, all of which, as Shakespeare and the scholars that studied his works used to point out, represent the enlightenment of human’s soul that strives for universal values. Shakespeare’s capability to create various characters of different intellect and social background, to follow them along some imaginative line, to give them thoughts and language, to make a connection between earthly and cosmic signs, symbols and events is also due to the very end of this drama. The end resembles very musch some kind of a new open space, a new horizon where the last scenes of the play take place. Having in mind Shakespeare’s position in the literary world, we can rightfully acquire the idea of his creations living through centuries  because he involved cosmic vision in them. That vision guides future writers, dramatists, philosophers to transformations of human mind and thoughts making them believe that this is where man’s elan vital (life force) lies.By analyzing parts of the play we shall point out social and cultural values that are also cherished today.
Keywords: Shakespeare; past; society; culture; language